Esteroide e triterpenos de espécies de qualea-bioatividade sobre mycobacterium tuberculosis - Nasser, Ana Lucia Martiniano [UNESP]; Pavan, Fernando Rogério [UNESP]; Boralle, Nivaldo [UNESP]; Zocolo, Guilherme Julião [UNESP]; Dos Santos, Lourdes Campaner [UNESP]; de Marchi, Mary Rosa Rodrigues [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Vilegas, Wagner [UNESP] (My University, 2013)
The chloroform extract of bark of the tropical tree Qualea parviflora (Vochysiaceae) was fractionated by column chromatography on silica gel, yielding triterpenes (lupeol, lupenone, betulin, epi-betulinic acid and friedelin) and a steroid (β-sitosterol). β-sitosterol, lupenone and lupeol were also identified in Q. grandiflora and Q. multiflora, while friedelin was detected only in Q. Multiflora, by means of gas chromatography-mass spectrometry. The anti-Mycobacterium tuberculosis activity of the chloroform extract and isolated compounds was assayed by MABA and MIC values ranged from 250.0 to 31.2 μg/mL. This study is the first to investigate the chemistry and antitubercular activity of apolar compounds from Qualea species.
Sterol and triterpenes from qualea species: Bioactivity on mycobacterium tuberculosis
Keywords: Anti-mycobacterium tuberculosis activity; Qualea species; Triterpenes